EDUCATION AND RELIGION IN NIGERIAN MULTI-ETHNIC SOCIETY AS FACTORS FOR NATIONAL UNITY AND INTEGRATION - Ishaq, Nuhu Jaafar; Aminu, Jabbi (Sokoto Educational Review, 2013)
Education is the bedrock for national unity and integration. In schools, through interaction with peers and mates from the different ethnic, religious and socio-economic background, children become socialized, integrated and united for they have one goal to achieve. This paper examines education and religion in Nigerian multi-ethnic society as factors for national unity and integration. The conceptual clarification of education, religion and ethnicity were made. Religious and ethnic problems in Nigerian schools were highlighted and discussed. Based on the points raised, the paper recommended among others that, religious and ethnic tolerance should be incorporated in the curriculum of both primary and secondary schools. This could be of great help in solving the religious and ethnic problems in Nigeria.